Penggunaan Alat Peraga Mistar Hitung Untuk Melatih Operasi Hitung Bilangan Bulat Pada Anak Sekolah Dasar - Hidayah Putri, Jihan; Bella Saragih, Risna Mira; Matondang, Khoiruddin (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
Mathematics learning at the elementary school level often faces serious obstacles when entering the material of integer arithmetic operations, which is caused by the abstract nature of the concept for students at the concrete operational stage. This community service activity aims to train and improve the ability of integer arithmetic operations in children at the Fadilla Rahma Foundation through the use of slide rule props. The implementation methods used in this service include interactive lectures, demonstrations of tool use, and guided independent exercises. The activity participants consisted of 15 elementary school students who were members of the skilled reading and numeracy classes. The results of this activity show a significant increase in students' knowledge and skills. Before the intervention, students had difficulty visualizing the direction of number movements on negative numbers, but after using the slide rule, students were able to master the calculation steps with an accuracy rate of 90%. The use of slide rule media has proven effective in transforming abstract concepts into concrete ones, making it easier for students to understand the logic of addition and subtraction of integers. In addition to cognitive improvement, this activity also succeeded in awakening students' motivation and self-confidence in working on mathematics problems. The conclusion of this service is that slide rule props are a very representative and effective learning medium to be used at the elementary school level to strengthen children's numeracy foundations. It is recommended for educators to continue integrating physical props in mathematics learning to create a meaningful and enjoyable learning experience.